Acute Kidney Injury in Critically Ill Cirrhotic Patients with Spontaneous Bacterial Peritonitis - Sanokulova Sitora Avazovna (Zien Journals, 2023)
Acute kidney injury (AKI) is an important independent predictor of mortality in cirrhotic patients with spontaneous bacterial peritonitis (SBP). However, the definition of AKI in cirrhosis has been debated for many years. This study aims to compare the prediction accuracy of Kidney Disease: Improving Global Outcomes (KDIGO) and International Club of Ascites (ICA) criteria for hospital mortality in cirrhotic patients with SBP admitted to the intensive care unit (ICU).
Keywords: cirrhosis; spontaneous bacterial peritonitis; acute kidney injury